Appraisal of fibroblast viability in different concentration of glucose as mimicry diabetic condition - Ebrahimi, Maryam; Rezaei Tavirani, Mostafa; Heidari Keshel, Saeed; Raeisossadati, Reza; Hoseinzade Salavati, Behrooz; Daneshimehr, Fatemeh (Archives of Advances in Biosciences, 2011)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Diabetes mellitus is a common name for a group of diseases of a much diversified etiopathogenesis, characterized by chronically increased concentration of blood glucose. Diabetes results from alterations of various genes, each having a partial and additive effect. The inheritance pattern is thus complex, and environmental factors play an important role in favoring or delaying the expression of the disease. Diabetes can cause devastating complications, including cardiovascular diseases, kidney failure, and blindness, leg and foot amputations, delay in wound healing, which often result in disability and death. Fibroblast cells play a critical role in wound healing. They are the most common cells of connective tissue in animals. Tissue damage stimulates fibrocystic and induces the mitosis of fibroblasts. Wound healing processes in diabetic patients are so longer and sometimes cause to cut damaged tissue. In this study Fibroblasts were isolated from foreskin and cultured as primary cell culture in different concentrations of glucose (8.8 mmol/l, 13.13 mmol/l, 18.31 mmol/l, 27.7 mmol/l, 37.18 mmol/l, 47.17 mmol/l, 83.24 mmol/l, 124.8 mmol/l and 166.4 mmol/l) for 48h incubation time. Traditionally, the determination of cell growth is done by counting viable cells after staining witha vital dye. Among several approaches have been used in the past, The MTT method of cell determination is most invaluable to cultures which are prepared in multiwall plates. This assay is a sensitive, quantitative and reliable colorimetric assay that measures viability, proliferation and activation of cells. The results of this preliminary study suggest that altered glucose concentrations may affect fibroblast behavior in ways that are important for tissue repair and wound healing. The cells had low level of confluency and viability and in high concentration fibroblast had very low cell division.